The effect of age on referral to an oncologist and receipt of chemotherapy among small cell lung cancer patients in Ontario, Canada. Issue 3 (May 2019) - Doherty, Jordan; Dawe, David E.; Pond, Gregory R.; Ellis, Peter M.
Abstract: Objectives: Small cell lung cancer (SCLC) represents a significant health burden. There is a lack of information about patterns of referral and treatment for older patients over 70 years of age, in comparison to younger patients with SCLC. Materials and methods: A population-based retrospective cohort study was undertaken for patients identified from the Ontario Cancer Registry, Canada. All cases of SCLC diagnosed between January 2000 and December 2010 were eligible. Data were extracted on demographic variables, treatment and outcome. Logistic regression analyses were performed as appropriate. Results: There were 9021 cases of SCLC, with 10% of cases ≥80 years and 32.8% of cases aged 70–79 years and 53% male. Older patients were less likely to be referred to a medical oncologist (OR 0.28 ≥ 80 years, OR 0.60 70–79 years) and less likely to receive chemotherapy (OR 0.19 ≥ 80 years, OR 0.52 70–79 years) compared to younger patients (age < 70). Age, higher comorbidity and prior receipt of home care services were all prognostic of a lower likelihood of referral to a medical oncologist and receipt of chemotherapy. Local health region was also prognostic for referral to and receipt of chemotherapy, indicative of significant regional variation in practice. Conclusions: Older patients with SCLC are less likely to be referred for treatment and less likely to receive treatment than younger patients. These data represent a potential gap in knowledge translation.